A Tunable Multifunctional Terahertz Asymmetric Transmission Device Hybrid With Vanadium Dioxide Blocks - Xu, Boli; Zhong, Renbin; Liang, Zekun; Fang, Zheng; Fang, Jianhui; Zhang, Huimin; Wu, Zhenhua; Zhang, Kaichun; Hu, Min; Liu, Diwei (Frontiers in Materials, 2022)
A tunable multifunctional terahertz metamaterial asymmetric transmission device is proposed. The device is composed of three layers from top to bottom, i.e., Ge–SiO2–Ge. The germanium layer with a VO_2 block enables it to work in two operating modes by controlling the state of the VO_2 blocks, thereby flexibly realizing asymmetric forward and backward transmission with specific polarization. The device is endowed with a more flexible design of electromagnetic systems, rendering it suitable for applications in polarization converters, polarization filters, and other polarization modulators.